Notched tensile strength for long- and short-fiber reinforced polyamide - Govindan Potti P.K.; Rao B.N.; Srivastava V.K. (My University, 2025)
The point stress criterion and the average stress criterion are applied for evaluating the notched tensile strength of injection-moulded plates with machined and moulded-in notches. Use is made of a characteristic length which is found to be geometry and material dependent. (C) 2000 Elsevier Science Ltd. All rights reserved.; A test program was conducted to evaluate the tensile strength of injection-molded plates with machined and molded-in notches. Two methods, the point stress criterion and the average criterion, are applied. Use is made of a characteristic length which is found to be geometry and material dependent.